2005
DOI: 10.1901/jaba.2005.113-04
|View full text |Cite
|
Sign up to set email alerts
|

Refining the Experimental Analysis of Academic Skills Deficits: Part I. An Investigation of Variables That Affect Generalized Oral Reading Performance

Abstract: Experimental analyses for improving reading fluency deficits have rarely targeted generalized increases in academic responding. As a consequence, the variables that may help students to generalize newly learned forms of academic responding like reading are not well understood. Furthermore, experimental analyses of reading fluency interventions have not systematically examined difficulty level as a variable that may affect instructional outcomes. The experiment reported in this paper expands (a) the measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 13 publications
2
32
0
Order By: Relevance
“…Greater differences across passages or at other levels of responding may yield different results. Nonetheless, the results are consistent with those of Daly et al (2005), who used the same procedures and found that all participants showed greater relative increases in harder materials and, for 1 participant, greater absolute levels of responding in harder materials. Therefore, future investigations will contribute to our understanding of the broader notion of instructional match by considering a wider range of performance levels and examining relative as well as absolute performance increases.…”
Section: Discussionsupporting
confidence: 87%
“…Greater differences across passages or at other levels of responding may yield different results. Nonetheless, the results are consistent with those of Daly et al (2005), who used the same procedures and found that all participants showed greater relative increases in harder materials and, for 1 participant, greater absolute levels of responding in harder materials. Therefore, future investigations will contribute to our understanding of the broader notion of instructional match by considering a wider range of performance levels and examining relative as well as absolute performance increases.…”
Section: Discussionsupporting
confidence: 87%
“…Adult modeling, RR, and phrase drill EC increased reading rates and decreased error rates on easy and difficult generalization passages with high content overlap (Daly et al, 2005). …”
Section: Resultsmentioning
confidence: 99%
“…Word supply with RR produced higher reading rates than phonics-based feedback with RR (i.e., sounding out miscues; Watson et al, 2009). RR with phrase drill EC and syllable segmentation and blending increased WCPM and decreased EPM (Daly et al, 2005). Finally, incorporating EC feedback during paired RR yielded gains in reading rate for below-, on-, and above-grade-level texts (Yurick et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Research in the area of reading has required application of the treatment strategy to generalization materials in order for observable improvements to be made , suggesting generalization is not spontaneous. Furthermore, only recently has research begun to experimentally investigate the specific conditions under which generalization in reading occurs (see Daly, Bonfiglio, Mattson, Persampieri, & Foreman-Yates, 2005), and we are unaware of generalization research with mathematics. Third, it might not be surprising that Anson's performance across generalization materials was undifferentiated, albeit within the mastery range, given that the results of the BEA and extended analysis suggested his academic problems were motivational.…”
Section: Discussionmentioning
confidence: 99%